Anti-oxidant properties of ficus religiosa L. Bark extract on human keratinocytes - Dixit, Shailesh S.; Kulkarni, Atul; Seo, Hyo Hyun; Gadgil, Jayant; Dingre, Medini; Umar, Ahmad; Moh, Sang Hyun; Parasharami, Varsha A. (Science of Advanced Materials, 2016)
Ficus religiosa (Sacred Fig) is a medicinally important tree, native to the Indian subcontinent. It has been extensively pharmacologically researched species having wide spectrum of medicinal properties. All parts of F. religiosa tree are known to possess important medicinal properties such as anti-oxidant, anti-inflammatory, wound healing and skin diseases etc. However, effects of F. religiosa on skin cells line HaCaT was not studied for its antioxidant properties. In this report we have investigated F. religiosa bark aqueous extract for its antioxidant properties on human keratinocytes (HaCaT) cell line using DPPH, superoxide dismutase 1, superoxide dismutase 2 and catalase assay. We observed that F. religiosa bark aqueous extract efficiently scavenged (80%) DPPH radicals. Superoxide dismutase1 assay of F. religiosa bark aqueous extract effectively scavenged superoxide radicals (O-2(-)) and showed dose dependent activity. Reactive oxygen species were trapped by superoxide dismutase 2 assay of F. religiosa bark aqueous extract and form hydrogen peroxide. Catalase assay results revelled that hydrogen peroxide was further decomposed to give water and oxygen. Thus various anti-oxidant assays of F. religiosa bark aqueous extract indicate that it efficiently reduced the reactive oxygen species in skin cells.
Keywords: Anti-Oxidant; Catalase Assay; DPPH Assay; Ficus religiosa; Keratinocyte HaCaT Cell Line; Moraceae; SOD Assay

Development of enhanced hypericin yielding transgenic plants and somaclones: high throughput direct organogenesis from leaf and callus explants of Hypericum perforatum - Khan, Shamshad A.; Verma, Priyanka; Arbat, Akshata; Gaikwad, Sushma; Parasharami, Varsha A. (Industrial Crops and Products, 2018)
Hypericum perforatum is well known for its anti-depressent properties due to the presence of hypericins and hyperforins. The direct regeneration protocol from leaf explants and Agrobacterium tumefaciens mediated genetic transformation is a prerequisite for gene transfer studies in this valuable plant system as H. perforatum has shown its recalcitrance to these studies previously. The aim of generating transgenic shoots or somaclones in the present study is to select high hypericine yielding H. perforatum plants. High throughput direct bud organogenesis from leaf explants has been achieved for the first time in this plant system on media combination of MS + 5.0 mg/l BAP + 1.0 mg/l. This medium interestingly also worked as the indirect regeneration media for generation of somaclones from callus cultures. Thus far optimized single media can be used for direct and indirect regeneration in H. perforatum. The direct regeneration frequency of plantlets from leaf explants was found to be 80% while 100% was the regeneration frequency noted for indirect plantlet regeneration from callus cultures. The optimized direct regeneration protocol from leaf explants was utilized for A. tumefaciens (harbouring pCAMBIA 1301) mediated genetic transformation studies with the aim of establishing transgenic lines of H. perforatum. The resultant study successfully gave rise to kanamycin resistant GUS positive shoots with transformation efficiency of 3136 +/- 3.6. A total of four transgenic H. perforatum clones namely T2, T3, T5 and T8 with different growth parameters were established, where highest of fivefold increase in hypericin content was recorded by T5 (276.8 +/- 9.2 mu g/g dry wt.) in comparison to control non transformed plants (35.6 +/- 2.7 mu g/g dry wt.). Interestingly the presence of serotonin and melatonin was also detected in transgenic plants on TLC basis. The transgenic nature of the plants was confirmed by PCR with amplification of uidA gene. Apart from it, from indirect regeneration from callus, total of ten somaclones were generated. The ISSR profiling of somaclones scored a total of 156 bands, among which 118 were polymorphic in nature. The glasshouse established soma clones showed up to twofold increase in hypericin content on HPLC analysis.
Keywords: Direct regeneration; Hypericin; Hypericum perforation; Indirect regeneration; ISSR; Somaclones; Transgenic plants

Enhanced anti-ageing and wound healing properties of Ficus religiosa L. bark, leaf and aerial root extract in human keratinocytes cell line (HaCaT) - Pandey, Prem; Seo, Hyo Hyun; Kim, Hye-In; Ryu, Seung Hwan; Dingre, Medini; Moh, Sang Hyun; Kulkarni, Atul; Parasharami, Varsha A. (Vegetos, 2020)
<span style="color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);">Plants have played a vital role in curative and preventive healthcare. <i style="box-sizing: inherit; color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);">Ficus religiosa<span style="color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);"> L., a medicinally important tree has been used as a traditional medicine to treat various ailments and skin diseases. However, its skin anti-ageing properties are not yet scientifically evaluated. Here we report the comparison of <i style="box-sizing: inherit; color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);">F. religiosa<span style="color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);"> bark (FRAqB), leaf (FRAqL) and aerial-roots (FRAqAR) extracts for skin anti-ageing and wound healing properties. FRAqB, FRAqL and FRAqAR extracts preparation, cell culture, RNA isolation, real time PCR, astringent activity and wound healing assay were carried out using standard methods. Axio Observer FL-microscope and ImageJ software were used for wound healing assay analysis. The real time PCR study reveals that matrix metalloproteinase-1 (MMP) RNA was downregulated to 75% and 95% for FRAqB and FRAqAR, respectively. For procollagen C-endopeptidase enhancer 1 (PCOLCE), FRAqB and FRAqL enhanced RNA levels by 500% and 300%, respectively. FRAqB and FRAqL increased wound healing area to about 60% and FRAqAR by 50%. All three extracts demonstrated astringent activity which is significant for skin tightening. The study proves that extracts of <i style="box-sizing: inherit; color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);">F. religiosa<span style="color: rgb(51, 51, 51); font-family: Georgia, Palatino, serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(252, 252, 252);"> are prominent candidates for pharmaceutical and cosmetic applications such as skin anti-ageing and wound healing.

Homo and heterologous expression of the HpPKS2 gene in Hypericum perforatum and Bacopa monnieri - Khan, Shamshad Ahmad; Verma, Priyanka; Parasharami, Varsha A. (Plant Cell Tissue and Organ Culture, 2022)
Hypericum perforatum has been known to produce hypericin and hyperforin that are used in treating mild to moderate depression. The HpPKS2 (H. perforatum polyketide synthase 2) gene is assumed to play a role in hypericin biosynthesis. The HpPKS2 gene was overexpressed in homologous H. perforatum in vitro grown plants through Agrobacterium tumefaciens-mediated genetic transformations. It leads to the establishment of seven glass house acclimatized transgenic lines. Among them, the HP12 transgenic plant showed 9.8 fold enhancement in hypericin content (379.4 +/- 10.3 mu g/g dry wt) followed by 3-fold in HP41 (117.1 +/- 4.5 mu g/g dry wt) as compared to control plants. This was further supported by the real-time PCR studies where it registered up to 5 fold enhancement of HpPKS2 gene expression. On the other hand, the heterologous expression of the HpPKS2 gene in Bacopa monnieri resulted in the establishment of five transgenic plant clones that were successfully acclimatized under glasshouse conditions. Among them, BT4 was found to be very slow-growing. The BT3 line showed maximum expression of the HpPKS2 gene which surprisingly also upregulates the expression of the other metabolic pathway genes of B. monierri namely isopentyl- diphosphate delta isomerase (IDDI), squaline synthase (SQS) and acetyl CoA C acetyltransferase (AA). The HPLC analysis in the heterologous system revealed the maximum production of bacopaside I (9.86 +/- 1.0 mg/g dry wt), bacopaside II (5.89 +/- 0.9 mg/g dry wt) and bacopasaponin C (3.59 +/- 0.3 mg/g dry wt) by transgenic lines BT8, BT3 and BT4, respectively. This enhancement in bacopaside I, bacopaside II and bacopasaponin C production was more than 26-fold, 5-fold and 21-fold, respectively in comparison to the control non transformed plants. Key message Overexpression of the HpPKS2 gene in H. perforatum led to higher hypericin content in the native system while its expression in the heterologous system i.e. B. monnieri also improves bacopaside I, bacopaside II and bacopasaponin C production.
Keywords: Agrobacterium tumefacience; Bacopa monnieri; Bacopasides; Heterologous expression; HpPKS2; Hypericin; Hypericum perforatum; Transgenics